'From innocence to experience: the representation of children in four documentary films'. Issue 3 (2nd September 2018) - Bruzzi, Stella
ABSTRACT: Children in front of the camera in nonfictional situations are fascinating and often unusually affecting. Quite possibly – and legitimately – the adult viewer might assume that children have not yet learnt how to 'perform', an oft-loaded term that carries connotations of inauthenticity and pretence and, in turn, signals the ability to be someone or something other than oneself. Stripped of knowingness, a child's tears or expressions of wonder become affecting because they seem genuine and spontaneous. This article looks in detail at four very different documentaries ('Seven Up!', Être et avoir, Capturing the Friedmans and Tarnation) in order to analyse notions of childhood innocence and performativity in front of the documentary camera. I intentionally compare documentaries from the pre-Smartphone era, when children take selfies several times a day and share images of themselves readily on social media. Cameras are now omnipresent, and children outperform adults when it comes to how to use them. Although we might still want to believe in the young child's 'innocence', ignorance of the camera or of the power dynamics of voyeurism are no longer corollaries of such 'innocence'.